THE USE OF HYPERBOLE AND METAPHORS IN POP SONG LYRICS: A COMPARATIVE STUDY ON TOP FIVE SONGS BY ARCTIC MONKEY AND COLDPLAY - Putri, Tharissa Adila; Nurrachman, Dian; Pramita, Agry (Saksama: Jurnal Sastra, 2024)
Comparative literature involves comparing, analysing and understanding literary works to explore similarities, differences and influences in literature. Comparative literature can be found in song lyrics as a way to create a better understanding and convey the songwriter's feelings or thoughts to the listener. This research explores the similarities and differences in the use of hyperbole and metaphor in the top five songs from Arctic Monkeys and Coldplay. By conducting a comparative analysis of the lyrical content, this research aims to reveal how these two well-known bands use these literary devices to convey emotions and themes in their music. By using Reaske's figurative language theory and objective criticism approach. This research found that Arctic Monkeys songs often explore themes of romance, emotion, and burning desire, using hyperbole to dramatically amplify feelings, making their expressions more intense and vivid, for Coldplay lyrics often raise themes of longing, regret, and admiration. As for metaphors, both bands use metaphors extensively to convey deeper meanings and evoke emotions. This research contributes to a deeper understanding of how literary techniques are used in songwriting across different genres and styles of music.Keywords: Arctic Monkeys, Coldplay, Comparative Literature, Figurative Language